2013
DOI: 10.1108/01439911311320859
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical equilibrium model of rubberless artificial muscle and application to position control of antagonistic drive system

Abstract: PurposeThe purpose of this paper is to describe a mechanical equilibrium model of a one‐end‐fixed type rubberless artificial muscle and the feasibility of this model for control of the rubberless artificial muscle. This mechanical equilibrium model expresses the relation between inner pressure, contraction force, and contraction displacement. The model validity and usability were confirmed experimentally.Design/methodology/approachPosition control of a one‐end‐fixed type rubberless artificial muscle antagonist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Hence, the second synthetic hydraulic fluid compatible material tested was a LDPE bag. One study has reported the use of rubber-less artificial muscles, and it utilized an aluminum vapor deposition polyester sheet for the bladder (Saito et al, 2013). Additionally, this group did not attach one end of the bladder to the other side of the muscle and ran them to a maximum pressure of only 1 bar.…”
Section: Bladder Materialsmentioning
confidence: 99%
“…Hence, the second synthetic hydraulic fluid compatible material tested was a LDPE bag. One study has reported the use of rubber-less artificial muscles, and it utilized an aluminum vapor deposition polyester sheet for the bladder (Saito et al, 2013). Additionally, this group did not attach one end of the bladder to the other side of the muscle and ran them to a maximum pressure of only 1 bar.…”
Section: Bladder Materialsmentioning
confidence: 99%
“…Here, the relation between the antagonistic force F A and the antagonistic position x, which is necessary to achieve the target stiffness K sys , is derived as follows by substituting (3) and (4) for (11).…”
Section: Mathematical Model Of Stiffness Of the Systemmentioning
confidence: 99%
“…However, no study has sufficiently examined how to set passive stiffness characteristics or how to measure actual stiffness characteristics when the position of the antagonistic drive system using an artificial muscle is controlled. Therefore, this study examines an antagonistic drive system using rubberless artificial muscle [11] to elucidate position control with passive stiffness. For this study, we derive a model of the rubberless artificial muscle as a variable stiffness element based approximately on isometric contraction characteristics.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the actuator has nonlinearities due to the effects of hysteresis, intrinsic to elastomers, presence of dead band and nonlinear Coulomb friction. The nonlinearities of the muscle added to the manipulator's kinematic and dynamics equations make the position tracking complex (Tondu and Lopez, 1997;Bogue, 2012;Saito et al, 2013;Kobayashi and Ito, 2015;Irshaidat et al, 2019).…”
Section: Introductionmentioning
confidence: 99%